Comparison of outcome and interventional complication rate in patients with acute stroke treated with mechanical thrombectomy with and without bridging thrombolysis. (22nd February 2016) - Weber, Ralph; Nordmeyer, Hannes; Hadisurya, Jeffrie; Heddier, Markus; Stauder, Michael; Stracke, Paul; Berger, Klaus; Chapot, Rene
Abstract : Background: No randomized trial has investigated the effect of mechanical thrombectomy (MT) alone in patients with acute stroke. There are conflicting results as to whether prior intravenous thrombolysis (IVT) facilitates subsequent MT, and data in patients treated with MT alone owing to contraindications to IVT are limited. Objective: To compare consecutive patients treated with MT alone or with preceding IVT in a large tertiary neurointerventional center, with special emphasis on contraindications to IVT. Methods: Retrospective analysis of 283 consecutive patients with acute ischemic stroke treated with MT in a tertiary neurovascular center over 14 months. Data on characteristics of periprocedural times, recanalization rate, complications, and long-term functional outcome were collected prospectively. Results: Information on prior IVT and functional outcome was available in 250 patients. Mean (SD) follow-up period was 5.7 (5.1) months and 105 (42%) patients received both IVT and MT. No significant differences were found in successful recanalization rates (Thrombolysis in Cerebral Infarction (TICI) 2b/3, 73.8% vs 73.1, p=0.952), complication rates, and long-term favorable outcome (modified Rankin Scale 0–2, 35.2% vs 40%, p=0.444) between patients receiving MT plus IVT and those receiving MT alone. A favorable outcome in patients directly treated with MT alone who were eligible for IVT was achieved in 48.2%. Thrombectomy was safe and resulted in a favorable outcome in 32% of patients with absolute contraindications to IVT. Conclusions: Preceding use of IVT was not an independent predictor of favorable outcome in patients with acute stroke treated with MT and complication rates did not differ whether or not IVT was used. MT is safe and achieved a favorable outcome in one-third of patients with stroke ineligible for IVT.